Studi Fenomenologi : Persepsi Ibu Bekerja yang Menyusui terhadap Dukungan Keluarga untuk Meningkatkan Keberhasilan ASI Eksklusif di Desa Pundungsari, Trucuk, Klaten - Titis Sensussiana; Ari Febru Nurlaily; Endang Zulaicha Susilaningsih (STIKES Karya Husada Kediri, 2022)
The progress of development of the times, has shifted the role of mothers as housewives becoming working mothers. However, shifting in the role of mothers as a working mothers will shift the duties of mothers as housewives. The process of breastfeeding is a natural process that the mothers performs after giving birth. with environmental that are developing and shifting caused the natural process of breastfeeding undergo difficulties. The process of exclusive breastfeeding, whish was supposed to run for six months, became unsuccessful due to the environment or lack of support from the environment. Family support is so significant in reaching exclusive breastfeeding. This support can be in the form of support of material, energy or thought. The purpose of the study is to know the perception of working mothers who breasfeed on family support to increase the success of exclusive breastfeeding in Pundungsari Village, Trucuk, Klaten. The study uses qualitative research methods by exploring about what is experienced by mothers who breastfeeding exclusively with family support. There are six informants of mothers who have successfully breastfed and an informant from posyandu cadres. The results of this study obtained four family support such instrumental, information, emotion and appreciation support. The support often done by instrumental support and emotional support. While information support is still minimal, the appreciation is not either. Keywords: Family support, exclusive breastfeeding, working mothers